1990
DOI: 10.1128/jcm.28.12.2797-2801.1990
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent enteric adenovirus variant not detected by commercial monoclonal antibody enzyme immunoassay

Abstract: A commercial monoclonal antibody enzyme immunoassay for the detection of enteric adenovirus types 40 and 41 (Ad4O and Ad4l) in stool specimens was evaluated. Twenty-one stool specimens from children with gastroenteritis, with adenovirus particles visible by electron microscopy, and reference strains Ad4O Dugan and Ad4l Tak were tested by Ad4O-and Ad4l-specific and adenovirus group-reactive immunoassays. AU stool specimens tested positive in the group-reactive immunoassay. However, only six specimens, containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The production of monoclonal antibodies to subgenus F adenoviruses [Herrmann et al, 1988;Wood et al, 19893 has allowed the development of commercial enzyme immunoassays as a n alternative to electron microscopy for diagnosis. However, recent studies have shown genomic variation within both type 40 and type 41, which may result in changes in the epitopes in the hexon region to which the monoclones are directed [Shinozaki et al, 1988; Van der Avoort et al, 1989;Scott-Taylor et al, 1990;de Jong et al, 19931. In the present study, we found a situation similar to that found by Scott-Taylor et al [ 19901 in their survey in Canada; 18 of 87 (21%) of the samples that proved to be adenovirus type 41 failed to be detected by 4liJH1 a monoclonal antibody raised to the prototype Ade 41 strain Tak [Herrmann et al, 1987a,bl. However, use of a Mab 4.3.1 raised against a virus obtained from a child in England detected 83 of 84 adenovirus 41 samples available for testing.…”
Section: Discussionmentioning
confidence: 99%
“…The production of monoclonal antibodies to subgenus F adenoviruses [Herrmann et al, 1988;Wood et al, 19893 has allowed the development of commercial enzyme immunoassays as a n alternative to electron microscopy for diagnosis. However, recent studies have shown genomic variation within both type 40 and type 41, which may result in changes in the epitopes in the hexon region to which the monoclones are directed [Shinozaki et al, 1988; Van der Avoort et al, 1989;Scott-Taylor et al, 1990;de Jong et al, 19931. In the present study, we found a situation similar to that found by Scott-Taylor et al [ 19901 in their survey in Canada; 18 of 87 (21%) of the samples that proved to be adenovirus type 41 failed to be detected by 4liJH1 a monoclonal antibody raised to the prototype Ade 41 strain Tak [Herrmann et al, 1987a,bl. However, use of a Mab 4.3.1 raised against a virus obtained from a child in England detected 83 of 84 adenovirus 41 samples available for testing.…”
Section: Discussionmentioning
confidence: 99%
“…This may have led to an underestimation, since 25 stools were considered EAd-positive after initial testing but failed to yield virus after culture. Also, highly specific monoclonal antibodies can fail to detect virus strains which have lost their determinants by antigenic drift (18), which can lead to underestimation. It may also be possible that higher rates of detection are due to outbreaks; the studies described by Cruz et al (6) and Tiemessen et al (20), in which high detection rates were found, were conducted over 1-year periods.…”
Section: Discussionmentioning
confidence: 99%
“…Seven were from Glasgow, United Kingdom (19), four were from Atlanta, Ga. 11, and seven were from Sandringham, Republic of South Africa (17,18). Seven fecal samples from the study of Scott-Taylor et al (24) were kindly provided by those authors. A collection of 57 fecal specimens were selected by negative-contrast electron microscopy (EM), immune EM (IEM), or DRE mapping in Manchester, United Kingdom (39).…”
Section: Materlals and Methodsmentioning
confidence: 99%